Corpus Integration in L2 Discipline-Specific Writing Courses: A Cross-Linguistic Didactic Intervention Study - Csürös, Karla; Gherasim, Claudiu; Chitez, Mădălina (Journal of Academic Writing, 2025)
This study evaluates the effectiveness of corpus-based interventions for enhancing writing skills in English L2 and French L2 among Romanian-speaking students. Following established intervention models, the study involved five stages: initial essay writing, corpus tool training, introduction to target language corpora, essay revision using corpora, and a satisfaction survey. Analysis of linguistic data (e.g., frequency lists, n-grams, and error correction rates) and survey responses from 40 participants reveals improvements in writing accuracy and diversity. Specifically, English L2 students demonstrated enhanced lexical accuracy and varied phraseology, while French L2 students improved syntactic precision and contextual use of academic terms. Both groups showed increased grammatical accuracy, especially in prepositions and articles, through corpus consultation. The findings underscore the pedagogical potential of corpora in writing instruction and the necessity of expanding corpus resources for under-resourced languages like French.